High-nickel ternary positive electrode material, preparation method thereof and battery cell
By introducing doped elements in the preparation process of the precursor of the ternary positive electrode material, a bond structure with high chemical bond strength is formed, and combined with high nickel and high voltage technology, the problem of existing materials being difficult to take into account high voltage, high capacity and long cycle life is solved, and the improvement of material performance and the reduction of battery cell cost is achieved.
Patent Information
- Application Number
- CN202411974293.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
It is difficult for existing ternary positive electrode materials to take into account the problems of high voltage, high capacity and long cycle life at the same time.
The liquid phase method is used to introduce two doped elements A and M respectively in the preparation process of the precursor to form A-O bonds and M-O bonds with high chemical bond strength to improve the microstructure of the material, and improve the structural stability and cyclic performance of the material through the combination of high nickel and high voltage.
It improves the structural stability and cycling performance of high-nickel ternary cathode materials at high voltages, enhances the reversible discharge capacity, meets the charging and discharge cycle life requirements, and helps to reduce the use of cathode materials and reduces the cost of the battery cell.
Smart Images

Figure CN119750668A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a high-nickel ternary positive electrode material and a preparation method and a battery cell thereof. Background Art
[0002] Ternary lithium-ion power batteries have the advantages of high energy density and long driving range. In recent years, they account for about 40% of the installed capacity of power batteries. x Co y Mn 1-x-y )O2(x≥0.8) is expensive, that is, the cost of positive electrode materials used in battery cells is relatively high. The development of low-cost high-nickel ternary positive electrode materials and battery cell design has the advantage of reducing costs and increasing efficiency.
[0003] High nickel and high voltage are important branches in the current development route of ternary positive electrode materials. Both can increase the theoretical and actual gram capacity of the material. High nickel has been developed to 8 series and 9 series products, and the material has the capacity for mass production. High voltage is mostly used in medium nickel (Ni <70mol%) products, and its voltage can be increased to 4.6V and above. How to effectively combine high nickel and high voltage while ensuring high capacity and long cycle life of the material is an important improvement direction for high nickel ternary positive electrode materials.
[0004] For example, the Chinese patent application with the patent authorization publication number CN 114436346A discloses a method for preparing a high-nickel ternary single crystal material precursor by using an alkaline composite dispersion liquid assisted coprecipitation method. The process is simpler, the particle size is controllable and the distribution is narrow, the morphology is uniform, the dispersion is high, the product consistency is good, and large-scale production can be achieved. The Chinese patent with the patent authorization publication number CN112531158B discloses a method for preparing a high-nickel ternary single crystal material by controlling the material precursor synthesis process and crushing and grading the precursor, mixing the precursor with a lithium source, first dehydrating at low temperature to obtain a pre-oxide, and then sintering at high temperature in a dynamic rotary furnace. The high-nickel ternary single crystal material prepared by this method has the characteristics of full primary particle morphology, uniform dispersion, complete crystal form, stable structure, and excellent electrochemical energy. The Chinese patent application with the patent authorization publication number CN117691101A discloses a method and application for preparing a high-voltage ternary positive electrode material by mixed calcination of Al and Ni additives, which also has the advantages of high cycle stability and high specific capacity. However, the ternary positive electrode materials obtained by the above preparation methods are difficult to achieve high voltage, high capacity and long cycle life at the same time. Summary of the invention
[0005] The main purpose of the present invention is to provide a high-nickel ternary positive electrode material and a preparation method and a battery cell, so as to solve the problem that the ternary positive electrode material in the prior art is difficult to achieve high voltage, high capacity and long cycle life at the same time.
[0006] In order to achieve the above-mentioned object, according to one aspect of the present invention, a method for preparing a high-nickel ternary positive electrode material is provided, and the preparation method comprises: step S1, mixing raw materials including a water-soluble compound containing element A, a nickel salt, a cobalt salt, a manganese salt and water to obtain a first mixed solution; step S2, mixing a water-insoluble compound containing element M with an organic solvent to obtain a second mixed solution; step S3, coprecipitating the raw materials including the first mixed solution and the second mixed solution under alkaline conditions to obtain a high-nickel ternary precursor; step S4, first sintering the raw materials including the lithium salt and the high-nickel ternary precursor to obtain the high-nickel ternary positive electrode material; wherein the chemical formula of the high-nickel ternary precursor is Ni x Co y Mn z A m M n (OH)2, A and M are each independently a doping element, A and M are each independently selected from any one or more of Ti, Nb, Zr, Te, W and Mo, x+y+z≥0.99, 0.8≤x<1, 0 <y<0.2,m+n≤0.01,m<0.01,n<0.01。
[0007] Furthermore, D of the above-mentioned high nickel ternary precursor 50 The particle size is 3 to 5 μm, and / or m is less than 0.005, n is less than 0.005, and / or m:n is equal to 0.1 to 10:1.
[0008] Furthermore, the total concentration of metal ions in the first mixed solution is 1.5 to 3 mol / L, and / or the total concentration of A ions in the first mixed solution is 1.5 to 30 mmol / L.
[0009] Furthermore, the total concentration of M ions in the second mixed solution is 0.015-0.3 mol / L; and / or the organic solvent is ethanol or an ethanol solution containing sodium hydroxide, wherein the pH value of the ethanol solution containing sodium hydroxide is 11-13.
[0010] Furthermore, the volume ratio of the first mixed solution to the second mixed solution is 1:0.005-1.
[0011] Furthermore, the pH value of the above coprecipitation is 11-12, and the pH value of the coprecipitation is controlled by ammonia water and NaOH solution; and / or the temperature of the coprecipitation is 50-60°C; and / or stirring is performed during the coprecipitation process, and the stirring speed is 400-600rpm.
[0012] Furthermore, the temperature of the first sintering is 850° C. to 950° C., the heating rate of the first sintering is 1 to 5° C. / min, and the time of the first sintering is 3 to 10 hours.
[0013] Furthermore, the preparation method also includes: performing a second sintering on the raw materials including the product obtained after the first sintering and the coating agent to obtain a high-nickel ternary positive electrode material; wherein the molar ratio of the product obtained after the first sintering to the coating agent is 1:0.0001~0.001; and / or the coating agent is selected from any one or more of Al2O3, BaO, MgCO3, V2O5 and B2O3; and / or the temperature of the second sintering is 500℃~800℃, the heating rate of the second sintering is 1~5℃ / min, and the time of the second sintering is 3~10h.
[0014] According to another aspect of the present invention, a high-nickel ternary positive electrode material is provided, and the high-nickel ternary positive electrode material is prepared by the above-mentioned preparation method.
[0015] According to another aspect of the present invention, there is provided a battery cell, comprising a positive electrode and a negative electrode, wherein the positive electrode comprises a positive electrode active material, and the negative electrode comprises a negative electrode active material, wherein the negative electrode active material is silicon graphite, and the positive electrode active material is the above-mentioned high-nickel ternary positive electrode material, wherein the operating voltage range of the battery cell is 2.75 to 4.35 V.
[0016] Applying the technical solution of the present invention, the present application introduces two doping elements, A and M, respectively, in the precursor preparation process by adopting a liquid phase method, and the introduced two doping elements A and M exist in the layered structure in the form of AO bonds and MO bonds with high chemical bond strength, thereby improving the microstructure of the high-nickel ternary positive electrode material and improving the structural stability and cycle performance of the high-nickel ternary positive electrode material under high voltage (full voltage ≥ 4.3V). At the same time, combining high nickel and high voltage, the reversible discharge gram capacity of the high-nickel ternary positive electrode material is further improved, which is beneficial to reduce the use of positive electrode materials on the basis of meeting the charge and discharge cycle life requirements, thereby helping to reduce the cost of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0018] Figure 1 The cycle capacity retention rate curves of Example 1, Comparative Example 1 and Comparative Example 2 of the present application at room temperature 1C / 1C are shown;
[0019] Figure 2The SEM image of the high-nickel ternary positive electrode material in Example 1 of the present application is shown;
[0020] Figure 3 The SEM image of the high-nickel ternary positive electrode material in Comparative Example 1 of the present application is shown;
[0021] Figure 4 The SEM image of the high-nickel ternary positive electrode material in Comparative Example 2 of the present application is shown;
[0022] Figure 5 The XRD diagrams of the high-nickel ternary positive electrode materials in Example 1, Comparative Example 1 and Comparative Example 2 of the present application are shown. DETAILED DESCRIPTION
[0023] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0024] As analyzed in the background technology of this application, there is a problem in the prior art that it is difficult for ternary positive electrode materials to simultaneously take into account high voltage, high capacity and long cycle life. This application provides a high-nickel ternary positive electrode material, a preparation method thereof, and a battery cell.
[0025] In a typical embodiment of the present application, a method for preparing a high-nickel ternary positive electrode material is provided, and the preparation method comprises: step S1, mixing raw materials including a water-soluble compound containing an element A, a nickel salt, a cobalt salt, a manganese salt and water to obtain a first mixed solution; step S2, mixing a water-insoluble compound containing an element M with an organic solvent to obtain a second mixed solution; step S3, under alkaline conditions, coprecipitating the raw materials including the first mixed solution and the second mixed solution to obtain a high-nickel ternary precursor; step S4, first sintering the raw materials including a lithium salt and the high-nickel ternary precursor to obtain a high-nickel ternary positive electrode material; wherein the chemical formula of the high-nickel ternary precursor is Ni x Co y Mn z A m M n (OH)2, A and M are each independently a doping element, A and M are each independently selected from any one or more of Ti, Nb, Zr, Te, W and Mo, x+y+z≥0.99, 0.8≤x<1, 0 <y<0.2,m+n≤0.01,m<0.01,n<0.01。
[0026] This application uses a liquid phase method to introduce two doping elements, A and M, respectively, during the precursor preparation process. The introduced two doping elements, A and M, exist in the layered structure in the form of AO bonds and MO bonds with high chemical bond strength, which improves the microstructure of the high-nickel ternary positive electrode material and improves the structural stability and cycle performance of the high-nickel ternary positive electrode material under high voltage (full voltage ≥ 4.3V). At the same time, combining high nickel and high voltage, the reversible discharge gram capacity of the high-nickel ternary positive electrode material can be further improved, which is conducive to reducing the use of positive electrode materials on the basis of meeting the charge and discharge cycle life requirements, thereby helping to reduce the cost of the battery cell.
[0027] In one embodiment of the present application, D of the high nickel ternary precursor 50 The particle size is 3 to 5 μm, and / or m is less than 0.005, n is less than 0.005, and / or m:n is equal to 0.1 to 10:1.
[0028] Optimally control the D of high nickel ternary precursors 50 The particle size within the above range is conducive to improving the consistency and uniform dispersion of high-nickel ternary positive electrode materials, thereby improving the compaction density and electrochemical performance of high-nickel ternary positive electrode materials. By controlling the doping concentration and the ratio of doping elements within the above range, it is conducive to effectively and uniformly improving the stability of the layered structure under high nickel concentration conditions, reducing the performance degradation caused by excessive doping, and thus maintaining good electrochemical activity and cycle stability under high voltage conditions.
[0029] In one embodiment of the present application, the total concentration of metal ions in the first mixed solution is 1.5 to 3 mol / L, and / or the total concentration of A ions in the first mixed solution is 1.5 to 30 mmol / L.
[0030] It is preferred to control the total concentration of metal ions in the first mixed solution within the above range, which is conducive to forming a denser particle structure, thereby improving the compaction performance of the high-nickel ternary positive electrode material and increasing the energy density of the battery. By controlling the total concentration of A ions within the above range, it is conducive to increasing its content and uniform dispersion in the high-nickel ternary positive electrode material, enhancing the microstructure of the high-nickel ternary positive electrode material, thereby helping to enhance the structural stability and electrochemical performance of the high-nickel ternary positive electrode material, and thus improving the cycle life and capacity of the battery.
[0031] In one embodiment of the present application, the total concentration of M ions in the second mixed solution is 0.015-0.3 mol / L; and / or the organic solvent is ethanol or an ethanol solution containing sodium hydroxide, wherein the pH value of the ethanol solution containing sodium hydroxide is 11-13.
[0032] It is preferred to control the range of the above conditions, which is beneficial to more uniformly coordinate with the metal ions in the first mixed solution during the co-precipitation process to form a high-nickel ternary precursor with higher structural stability, thereby helping to enhance the structural stability and electrochemical properties of the high-nickel ternary positive electrode material at high voltage, and improve the cycle life and capacity of the battery.
[0033] In one embodiment of the present application, the volume ratio of the first mixed solution to the second mixed solution is 1:0.005-1.
[0034] Preferably, the range of the above conditions is controlled, which helps to control the doping amount of the A element and the M element in the high-nickel ternary positive electrode material and improves the uniform dispersion of the doping elements in the high-nickel ternary positive electrode material.
[0035] In one embodiment of the present application, the pH value of the above co-precipitation is 11-12, and the pH value of the co-precipitation is controlled by ammonia water and NaOH solution; and / or the temperature of the co-precipitation is 50-60°C; and / or stirring is performed during the co-precipitation process, and the stirring speed is 400-600rpm.
[0036] It is preferred to control the coprecipitation conditions within the above range, which is beneficial to improving the efficiency and effect of coprecipitation.
[0037] In one embodiment of the present application, the temperature of the first sintering is 850° C. to 950° C., the heating rate of the first sintering is 1 to 5° C. / min, and the time of the first sintering is 3 to 10 hours.
[0038] It is preferred to control the first sintering conditions within the above range, which is conducive to forming a complete crystalline structure and improving the structural stability of the high-nickel ternary positive electrode material.
[0039] In one embodiment of the present application, the preparation method further includes: performing a second sintering on a raw material including a product obtained after the first sintering and a coating agent to obtain a high-nickel ternary positive electrode material; wherein the molar ratio of the product obtained after the first sintering to the coating agent is 1:0.0001~0.001; and / or the coating agent is selected from any one or more of Al2O3, BaO, MgCO3, V2O5 and B2O3; and / or the temperature of the second sintering is 500℃~800℃, the heating rate of the second sintering is 1~5℃ / min, and the time of the second sintering is 3~10h.
[0040] By controlling the type of coating agent and the conditions of secondary sintering within the above range, it is beneficial to coat a dense coating layer on the surface of the high-nickel ternary positive electrode material, thereby further improving the cycle stability of the high-nickel ternary positive electrode material under high voltage, reducing capacity attenuation during the cycle process, and at the same time increasing the electronic conductivity of the high-nickel ternary positive electrode material and improving the overall performance of the battery.
[0041] In another typical embodiment of the present application, a high-nickel ternary positive electrode material is provided, and the high-nickel ternary positive electrode material is prepared by the above-mentioned preparation method.
[0042] The high-nickel ternary positive electrode material prepared by the above preparation method has better cycle stability and electrochemical performance, which is beneficial to improving the capacity and cycle life of the battery and reducing the use cost of the positive electrode material.
[0043] In another typical embodiment of the present application, a battery cell is provided, including a positive electrode and a negative electrode, the positive electrode includes a positive electrode active material, the negative electrode includes a negative electrode active material, the negative electrode active material is silicon graphite, and the positive electrode active material is the above-mentioned high-nickel ternary positive electrode material, wherein the operating voltage range of the battery cell is 2.75~4.35V.
[0044] The battery cell in this application adopts a combination of high-nickel ternary positive electrode material and silicon-graphite negative electrode, and optimizes the working voltage range of the battery cell, which is conducive to meeting the high nickel and high voltage performance of the battery cell, so that the battery cell shows higher energy density and long cycle life at high voltage, reduces costs, and improves the overall performance of the battery, thereby meeting the needs of new energy vehicles and energy storage systems for high energy density and long-life batteries. In addition, the above battery cell can be any one of soft pack, square shell, and cylindrical.
[0045] The following parameters are optimized during the preparation of the battery cell of this application:
[0046] During the preparation of the battery cell, the mass ratio of positive electrode active material: conductive agent: binder is 95-98:1-3:1-2;
[0047] During the preparation of the battery cell, the mass ratio of negative electrode active material: conductive agent: binder is 95-96:1-2:1-3;
[0048] The surface density of the positive electrode is designed to be 340-360g / m during the preparation of the battery cell. 2 ;
[0049] The negative electrode surface density is designed to be 200-210 g / m during the cell preparation process. 2 ;
[0050] The compaction density of the positive electrode sheet during the battery cell preparation process is designed to be 3.4-3.5 g / m 3 ;
[0051] The compaction density of the negative electrode sheet during the cell preparation process is designed to be 1.6-1.7 g / m 3 ;
[0052] During the preparation of the battery cell, the diaphragm is set to be a conventional ceramic diaphragm, specifically including a base film and an alumina ceramic layer coated on both sides of the base film; wherein the base film uses a polyolefin material with a thickness of 9 μm, and the thickness of the single-layer alumina ceramic layer is 1.5 μm;
[0053] During the preparation of the battery cell, the electrolyte is set to be a fluorocarbonate electrolyte, wherein the organic solvent is a mixed solvent of ethylene carbonate and diethyl carbonate, the mass ratio of the two is 1:2-3, the lithium salt uses 1M LiPF6, and the additive is a mixed additive of fluoroethylene carbonate and vinylene carbonate, the two respectively account for 2-5% and 0.5-2% of the total mass of the electrolyte (the organic solvent, the lithium salt and the additive are mixed);
[0054] During the preparation of the battery cell, the injection coefficient is set at 2 to 4 g / Ah;
[0055] During the preparation of the battery cell, the ratio of the negative electrode capacity to the positive electrode capacity is set to (N / P ratio) 1.05-1.15:1;
[0056] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0057] Example 1
[0058] According to the precursor Ni 0.896 Co 0.049 Mn 0.049 Nb 0.003 Ti 0.003 Nickel sulfate, cobalt sulfate, manganese sulfate and water-soluble niobium oxalate were mixed and dissolved in a certain amount of deionized water in a stoichiometric ratio of (OH)2 to obtain a mixed solution I, and the total concentration of metal ions in the mixed solution I was 2 mol / L, wherein the total concentration of niobium ions in the mixed solution I was 6 mmol / L, and the mixed solution I was pumped into the reactor for 2.5 h at a speed of 160 L / h.
[0059] According to the precursor Ni 0.896 Co 0.049 Mn 0.049 Nb 0.003 Ti 0.003 Ethanol titanium (ethyl titanate) is dissolved in a certain amount of ethanol in the stoichiometric ratio of (OH)2 to obtain a mixed solution II, and the total concentration of titanium ions in the mixed solution II is 0.05 mol / L. The mixed solution II is pumped into the reactor for 1 hour at a speed of 48 L / h.
[0060] Mixed solution I, mixed solution II, ammonia solution and NaOH solution were flowed into the reactor, wherein the volume ratio of mixed solution I to mixed solution II was 1:0.12, and the amount of ammonia solution and NaOH solution added was adjusted so that the pH value of the solution in the reactor was 11.6. When the solution temperature was 60°C and the stirring speed was 500 rpm, a coprecipitation reaction occurred. After the reaction was completed, centrifugation, drying and sieving were performed to obtain D 50 High nickel ternary precursor Ni with a particle size of 3 μm 0.896 Co 0.049 Mn 0.049 Nb 0.003 Ti 0.003 (OH)2.
[0061] In an oxygen atmosphere, the D 50 High nickel ternary precursor Ni with a particle size of 3 μm 0.896 Co 0.049 Mn 0.049 Nb 0.003 Ti 0.003 (OH)2 and lithium salt (LiOH·H2O) are mixed evenly, and the molar ratio of the precursor to the lithium salt is 1:1.04. The temperature is raised to 925°C at a heating rate of 2°C / min and then the first sintering is performed. After the first sintering for 6 hours, the central core of the high-nickel ternary material is obtained. Then the central core of the high-nickel ternary material is mixed evenly with B2O3, and the molar ratio of the central core of the high-nickel ternary material to B2O3 is 1:0.0003. The temperature is raised to 650°C at a heating rate of 2°C / min and then the second sintering is performed. After the first sintering for 4 hours, the high-nickel ternary positive electrode material is obtained;
[0062] The high nickel ternary positive electrode material is used as the positive electrode active material and the silicon graphite is used as the negative electrode active material to finally make a 1.7Ah soft pack battery cell. The following parameters are optimized during the preparation of the battery cell:
[0063] The mass ratio of positive electrode active material: conductive agent: binder in the battery cell preparation process is 97.8:1.2:1.0;
[0064] The mass ratio of negative electrode active material: conductive agent: binder in the battery cell preparation process is 95:2:3;
[0065] The surface density of the positive electrode is designed to be 350g / m during the preparation of the battery cell. 2 ;
[0066] The negative electrode surface density is designed to be 206g / m during the cell preparation process. 2 ;
[0067] The compaction density of the positive electrode sheet during the cell preparation process is designed to be 3.45g / m 3 ;
[0068] The compaction density of the negative electrode sheet during the cell preparation process is designed to be 1.65g / m 3 ;
[0069] During the preparation of the battery cell, the diaphragm is set to be a conventional ceramic diaphragm, specifically including a base film and an alumina ceramic layer coated on both sides of the base film; wherein the base film uses a polyolefin material with a thickness of 9 μm, and the thickness of the single-layer alumina ceramic layer is 1.5 μm;
[0070] During the preparation of the battery cell, the electrolyte is set to be a fluorocarbonate electrolyte, wherein the organic solvent is a mixed solvent of ethylene carbonate and diethyl carbonate, the mass ratio of the two is 3:7, the lithium salt uses 1M LiPF6, and the additive is a mixed additive of fluoroethylene carbonate and vinylene carbonate, the two respectively account for 3% and 1% of the total mass of the electrolyte (the organic solvent, lithium salt, and additive are mixed);
[0071] The injection coefficient during the cell preparation process is set at 2.8g / Ah;
[0072] During the preparation of the battery cell, the ratio of the negative electrode capacity to the positive electrode capacity was set to (N / P ratio) 1.08:1.
[0073] Example 2
[0074] The difference from Example 1 is that according to the precursor Ni 0.896 Co 0.049 Mn 0.049 Nb 0.003 Ti 0.003 Ethanol titanium (ethyl titanate) was dissolved in a certain amount of ethanol dissolved with sodium hydroxide (the pH value of the sodium hydroxide-ethanol solution was 12) in a stoichiometric ratio of (OH)2 to obtain a mixed solution II (the titanium ion concentration in the mixed solution II, the volume ratio of the mixed solution I to the mixed solution II, the pumping time and the speed were all consistent with those in Example 1), and finally a 1.7Ah soft-pack battery cell was made.
[0075] Example 3
[0076] The difference from Example 1 is that the total concentration of metal ions in mixed solution I is 1.5 mol / L, the total concentration of niobium ions in mixed solution I is 1.5 mmol / L; the total concentration of titanium ions in mixed solution II is 0.015 mol / L, the volume ratio of mixed solution I to mixed solution II is 1:1, the pumping speeds of mixed solution I and mixed solution II are both 50 L / h, and the time is both 2 h (the other parameters are consistent with Example 1), and finally a 1.7 Ah soft-pack battery cell is prepared.
[0077] Example 4
[0078] The difference from Example 1 is that the total concentration of metal ions in mixed solution I is 3 mol / L, the total concentration of niobium ions in mixed solution I is 30 mmol / L, the total concentration of titanium ions in mixed solution II is 0.3 mol / L, the volume ratio of mixed solution I to mixed solution II is 1:0.01, the pumping speeds of mixed solution I and mixed solution II are 200 L / h and 5 L / h, and the time is 2.5 h and 1 h respectively (the other parameters are consistent with Example 1), and finally a 1.7 Ah soft-pack battery cell is prepared.
[0079] Example 5
[0080] The difference from Example 1 is that the total concentration of metal ions in mixed solution I is 5 mol / L, the total concentration of niobium ions in mixed solution I is 50 mol / L; the total concentration of titanium ions in mixed solution II is 0.5 mol / L (the other parameters are consistent with Example 1), and finally a 1.7Ah soft-pack battery cell is prepared.
[0081] Example 6
[0082] The difference from Example 1 is that the total concentration of metal ions in mixed solution I is 1.5 mol / L, the total concentration of niobium ions in mixed solution I is 15 mmol / L, the total concentration of titanium ions in mixed solution II is 0.3 mol / L, the volume ratio of mixed solution I to mixed solution II is 1:0.005, the pumping speeds of mixed solution I and mixed solution II are 200 L / h and 5 L / h, and the time is 5 h and 1 h respectively (the other parameters are consistent with Example 1), and finally a 1.7 Ah soft-pack battery cell is prepared.
[0083] Example 7
[0084] The difference from Example 1 is that the total concentration of titanium ions in the mixed solution II is 0.005 mol / L, the volume ratio of the mixed solution I to the mixed solution II is 1:1.2, the pumping speeds of the mixed solution I and the mixed solution II are 60 L / h and 50 L / h, and the time is 2 h (the other parameters are consistent with Example 1), and finally a 1.7 Ah soft-pack battery cell is prepared.
[0085] Example 8
[0086] The difference from Example 1 is that the amount of ammonia solution and NaOH solution added is adjusted so that the pH value of the solution in the reactor is 11, and finally a 1.7Ah soft-pack battery cell is prepared.
[0087] Example 9
[0088] The difference from Example 1 is that the amount of ammonia solution and NaOH solution added is adjusted so that the pH value of the solution in the reactor is 12, and finally a 1.7Ah soft-pack battery cell is produced.
[0089] Example 10
[0090] The difference from Example 1 is that the amount of ammonia solution and NaOH solution added is adjusted so that the pH value of the solution in the reactor is 13, and finally a 1.7Ah soft-pack battery cell is prepared.
[0091] Embodiment 11
[0092] The difference from Example 1 is that the temperature of the first sintering is 850° C., and a 1.7Ah soft-pack battery cell is finally manufactured.
[0093] Example 12
[0094] The difference from Example 1 is that the temperature of the first sintering is 950° C., and a 1.7Ah soft-pack battery cell is finally manufactured.
[0095] Example 13
[0096] The difference from Example 1 is that the temperature of the first sintering is 1000° C., and a 1.7Ah soft-pack battery cell is finally manufactured.
[0097] Embodiment 14
[0098] The difference from Example 1 is that the molar ratio of the central core of the high-nickel ternary material to B2O3 is 1:0.0001, and a 1.7Ah soft-pack battery cell is finally made.
[0099] Embodiment 15
[0100] The difference from Example 1 is that the molar ratio of the central core of the high-nickel ternary material to B2O3 is 1:0.001, and a 1.7Ah soft-pack battery cell is finally made.
[0101] Example 16
[0102] The difference from Example 1 is that the molar ratio of the central core of the high-nickel ternary material to B2O3 is 1:0.002, and a 1.7Ah soft-pack battery cell is finally made.
[0103] Embodiment 17
[0104] The difference from Example 1 is that the central core of the high-nickel ternary material is not coated with B2O3, and the high-nickel ternary positive electrode material is directly used as a high-nickel ternary positive electrode material to finally make a 1.7Ah soft-pack battery cell.
[0105] Comparative Example 1
[0106] According to the precursor Ni 0.90 Co 0.05 Mn 0.05Nickel sulfate, cobalt sulfate and manganese sulfate were mixed and dissolved in a certain amount of deionized water in a stoichiometric ratio of (OH)2 to obtain a mixed solution, and the total concentration of metal ions in the mixed solution was 2 mol / L; the mixed solution, ammonia solution and NaOH solution were flowed into a reactor, and the amount of ammonia solution and NaOH solution added was adjusted so that the pH value of the solution in the reactor was 11.6. When the solution temperature was 60°C and the stirring speed was 500 rpm, a coprecipitation reaction occurred. After the reaction was completed, centrifugation, drying and sieving were performed to obtain D 50 High nickel ternary precursor Ni with a particle size of 3 μm 0.90 Co 0.05 Mn 0.05 (OH)2.
[0107] In an oxygen atmosphere, the D 50 High nickel ternary precursor Ni with a particle size of 3 μm 0.90 Co 0.05 Mn 0.05 (OH)2, lithium salt (LiOH·H2O), Nb2O5 and TiO2 are mixed evenly, the molar ratio of the precursor to the lithium salt is 1:1.04, and the first sintering is carried out after the temperature is increased to 925°C at a heating rate of 2°C / min. After the first sintering for 6 hours, the central core of the high-nickel ternary material is obtained; then the central core of the high-nickel ternary material is mixed evenly with B2O3, and the molar ratio of the central core of the high-nickel ternary material to B2O3 is 1:0.0003, and the second sintering is carried out after the temperature is increased to 650°C at a heating rate of 2°C / min. After the first sintering for 4 hours, the high-nickel ternary positive electrode material is obtained.
[0108] The high-nickel ternary positive electrode material is used as the positive electrode active material and the silicon-graphite is used as the negative electrode active material to finally make a 1.7Ah soft-pack battery cell.
[0109] Comparative Example 2
[0110] The difference from Example 1 is that niobium oxalate and ethyl titanium (ethyl titanate) are dissolved together in deionized water to obtain a mixed solution, the concentration of niobium ions in the mixed solution is the same as the total concentration of niobium ions in mixed solution I of Example 1, and the amount of titanium ions added to the mixed solution is consistent with the amount of titanium ions introduced in Example 1, and finally a 1.7Ah soft-pack battery cell is prepared.
[0111] Performance Test:
[0112] The soft-pack cells of the above embodiments and comparative examples were tested. Specifically, the operating voltage range was set to 2.75-4.35 V, and the reversible gram capacity of the positive electrode at 0.33 C and the capacity retention rate after 1200 cycles of 1C / 1C at room temperature were measured. Table 1 is a statistical list of the test results. At the same time, the chemical formulas of the high-nickel ternary positive electrode materials obtained in the embodiments and comparative examples are listed in Table 1.
[0113] Table 1
[0114]
[0115]
[0116] The ICP results of the high nickel ternary positive electrode materials of Example 1, Comparative Example 1 and Comparative Example 2 are shown in Table 2.
[0117] Table 2
[0118] Implementation / Comparative Example Ni(mol%) Co(mol%) Mn (mol%) Nb(ppm) Ti(ppm) Example 1 89.59 4.89 4.89 2931 3047 Comparative Example 1 89.57 4.89 4.90 3026 3010 Comparative Example 2 89.62 4.97 4.98 3182 986
[0119] The XRD refined cell parameter results of the high nickel ternary positive electrode materials of Example 1, Comparative Example 1 and Comparative Example 2 are shown in Table 3, wherein a represents the length of the unit cell along the a-axis (a single direction of the plane); c represents the length of the unit cell along the c-axis (vertical direction, perpendicular to the plane where the a-axis is located); c / a refers to the ratio of c to a, which represents the growth priority ability of the unit cell along a certain direction; V refers to the volume of the unit cell; I 003 / I 104 Refers to the ratio of the two main peaks of diffraction intensity in a material, which is used to evaluate the layered structure characteristics of the material.
[0120] Table 3
[0121] Implementation / Comparative Example a c c / a V <![CDATA[I 003 / I 104 <!-- 9 -->]]> Example 1 2.86416 14.27932 4.98552 101.45 3.0116 Comparative Example 1 2.87712 14.19749 4.93462 101.78 1.6083 Comparative Example 2 2.86673 14.26618 4.97646 101.53 2.5302
[0122] The cycle capacity retention rate curves of Example 1, Comparative Example 1 and Comparative Example 2 of the present application at room temperature 1C / 1C are as follows: Figure 1 As shown. Figure 1 It can be seen that the capacity retention rate of 1C / 1C cycle at room temperature: the capacity retention rate of Example 1 after 1200 cycles is 81.95%, while the capacity retention rates of Comparative Examples 1 and 2 after 1200 cycles are 73.79% and 74.61%, respectively. It can be seen that the capacity retention rate advantage of Example 1 is >3%. The reason is: Example 1 introduces the doping metal through a step-by-step solvent method, so that the metal is evenly distributed in the bulk phase of the precursor, and the degree of bonding between AO bonds and MO bonds is higher. Most of the metal elements introduced by solid phase sintering in Comparative Example 1 are located on the surface of the precursor particles, and do not enter the bulk structure too much, resulting in a decrease in the degree of bonding between AO bonds and MO bonds. Comparative Example 2 uses a one-step solvent method to introduce the dopant, and the water-soluble element A can be used between the main element Ni / Co / Mn ions and OH - During the bonding process, the water-insoluble M element dopant is evenly dispersed into the layered structure, while the non-water-soluble M element dopant cannot be evenly dispersed, resulting in a reduction in the doping amount entering the crystal structure (bulk and surface) compared to the designed value.
[0123] The SEM images of the high nickel ternary positive electrode materials in Example 1, Comparative Example 1 and Comparative Example 2 of the present application are shown in the following order: Figure 2 , Figure 3 and Figure 4 . From the results of the surface morphology, it can be seen that since Example 1 and Comparative Example 2 use the co-precipitation solvent method to introduce the doping elements, the surface point-like coating marks are less and the particles are smoother. However, since Comparative Example 1 uses the solid-phase sintering method for doping, its surface point-like doping coating marks are more. Combined with the data in Table 2, it can be seen that the measured contents of doping elements A and M in Example 1 are very close to the designed values, thanks to the good dispersibility of the two elements during the co-precipitation process. Comparative Example 1 uses the solid-phase sintering method to introduce A and M element dopants, which are more concentrated on the surface, and the subsequent treatment process does not separate from the material system, so that the actually measured A and M element contents are close to the designed values. In Comparative Example 2, since the M element dopant is non-water-soluble, it does not fully and completely enter the co-precipitation product, and its content in the precursor and the ternary finished material is much lower than the designed value.
[0124] The XRD patterns of the high nickel ternary positive electrode materials in Example 1, Comparative Example 1 and Comparative Example 2 of the present application are as follows: Figure 5 As shown, Figure 5 Here 2θ represents the angle between the incident X-ray and the diffraction detector.
[0125] Example 1, Comparative Example 1 and Comparative Example 2 all belong to the hexagonal structure of α-NaFeO2, and the main peak (003) signal peak intensity is obvious, corresponding to the typical layered structure. Combined with the data in Table 3, it can be seen that the XRD refinement results show that the c-axis of the unit cell parameter of the material obtained in Example 1 increases, corresponding to the increase in the c / a value, that is, the interlayer spacing is enlarged, I 003 / I 104 The increase indicates that it makes the unit cell grow preferentially along the c-axis to a certain extent. The reason is that the metal elements A and M enter the bulk structure, and their atomic radius is larger and their ability to combine with O is stronger. In Comparative Example 2, the A element also enters the bulk structure smoothly through the liquid phase coprecipitation process, while the M element is not successfully introduced due to the difference in solubility. Its c-axis, c / a value, I 003 / I 104 Compared with Example 1, the doping elements in Comparative Example 1 are concentrated on the particle surface due to the solid phase sintering method, which has little effect on the unit cell parameters in the bulk phase. 003 / I 104 Minimum, that is, the interlayer spacing is minimum.
[0126] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0127] This application uses a step-by-step liquid phase method to introduce two doping elements, A and M, respectively, during the precursor preparation process. The introduced two doping elements A and M exist in the layered structure in the form of AO bonds and MO bonds with high chemical bond strength, which improves the microstructure of the high-nickel ternary positive electrode material and improves the structural stability and cycle performance of the high-nickel ternary positive electrode material under high voltage (full voltage ≥ 4.3V). At the same time, combining high nickel and high voltage, the reversible discharge gram capacity of the high-nickel ternary positive electrode material can be further improved, which is conducive to reducing the use of positive electrode materials on the basis of meeting the charge and discharge cycle life requirements, thereby helping to reduce the cost of the battery cell.
[0128] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-nickel ternary positive electrode material, characterized in that: The preparation method comprises: Step S1, mixing raw materials including a water-soluble compound containing element A, a nickel salt, a cobalt salt, a manganese salt and water to obtain a first mixed solution; Step S2, mixing the water-insoluble compound containing the M element with an organic solvent to obtain a second mixed solution; Step S3, co-precipitating the raw materials including the first mixed solution and the second mixed solution under alkaline conditions to obtain a high-nickel ternary precursor; Step S4, performing a first sintering on the raw materials including the lithium salt and the high-nickel ternary precursor to obtain a high-nickel ternary positive electrode material; The general chemical formula of the high nickel ternary precursor is Ni x Co y Mn z A m M n (OH)2, A and M are each independently a doping element, and A and M are each independently selected from any one or more of Ti, Nb, Zr, Te, W and Mo, x+y+z≥0.99, 0.8≤x<1, 0 <y<0.2,m+n≤0.01,m<0.01,n<0.01。 2. The preparation method according to claim 1, characterized in that: The D 50 The particle size is 3 to 5 μm, and / or m is less than 0.005, n is less than 0.005, and / or m:n is equal to 0.1 to 10:
1.
3. The preparation method according to claim 1 or 2, characterized in that: The total concentration of metal ions in the first mixed solution is 1.5 to 3 mol / L, and / or the total concentration of A ions in the first mixed solution is 1.5 to 30 mmol / L.
4. The preparation method according to any one of claims 1 to 3, characterized in that The total concentration of M ions in the second mixed solution is 0.015-0.3 mol / L; and / or the organic solvent is ethanol or an ethanol solution containing sodium hydroxide, wherein the pH value of the ethanol solution containing sodium hydroxide is 11-13.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The volume ratio of the first mixed solution to the second mixed solution is 1:0.005-1.
6. The preparation method according to any one of claims 1 to 5, characterized in that The pH value of the coprecipitation is 11-12, and the pH value of the coprecipitation is controlled by ammonia water and NaOH solution; and / or the temperature of the coprecipitation is 50-60° C.; and / or stirring is performed during the coprecipitation, and the stirring speed is 400-600 rpm.
7. The preparation method according to any one of claims 1 to 6, characterized in that The temperature of the first sintering is 850° C. to 950° C., the heating rate of the first sintering is 1 to 5° C. / min, and the time of the first sintering is 3 to 10 hours.
8. The preparation method according to any one of claims 1 to 7, characterized in that The preparation method further comprises: Performing a second sintering on the raw material including the product obtained after the first sintering and the coating agent to obtain the high-nickel ternary positive electrode material; Wherein, the molar ratio of the product obtained after the first sintering to the coating agent is 1:0.0001-0.001; and / or the coating agent is selected from any one or more of Al2O3, BaO, MgCO3, V2O5 and B2O3; And / or the temperature of the second sintering is 500° C. to 800° C., the heating rate of the second sintering is 1 to 5° C. / min, and the time of the second sintering is 3 to 10 hours.
9. A high-nickel ternary positive electrode material, characterized in that: The high-nickel ternary positive electrode material is prepared by the preparation method described in any one of claims 1 to 8.
10. A battery cell, comprising a positive electrode and a negative electrode, wherein the positive electrode comprises a positive electrode active material, the negative electrode comprises a negative electrode active material, and the negative electrode active material is silicon-graphite, characterized in that: The positive electrode active material is the high-nickel ternary positive electrode material as described in claim 9, wherein the operating voltage range of the battery cell is 2.75 to 4.35V.
Citation Information
Patent Citations
A high-nickel ternary single crystal material and its preparation method
CN112531158B
Method for preparing high-nickel ternary single crystal material precursor through coprecipitation method
CN114436346A
High-voltage ternary positive electrode material and preparation method and application thereof
CN117691101A
Blended cathode materials
CN103828099A
Preparation method of Mg and Ti composite doped lithium-rich manganese based positive electrode material
CN106711439A